Green Barriers and China’s Agricultural Product Export: Is There a Relationship? - Hang, Fei (2012)
In recent years, the world economic integration trend has become more apparent, and the trades among different countries have been strengthened, coming with increasingly close relationship and more incentive competition (China Daily, 2012). But with the changes of international trade environment and lower tariff barriers, some countries are increasingly putting out a series of new trade protection measures to achieve the purpose of trade protection. The green barrier is one of the most frequent measures in developed countries from the 1990’s (Feng, 2009). As an agricultural country, the export of China’s agricultural products are often suffered the restrictions from the green barriers. The positive green barriers can regulate the agricultural production in China, and promote the agricultural development and international trade, on the other hand, the objective green barriers would increase the cost of trading, even cause trade friction, and prevent the development of international trade (Wang & Liu, 2007). So the research of influence of green barriers on China’s agricultural products is very realistic. According to the influence of green barriers on China’s agricultural exports, the corresponding countermeasures can be made to deal with the green barriers and improved China’s competitiveness in the international competition. However, most of the existing studies about green barriers focus on the descriptive analysis. This study of the influence of green barriers on China’s agricultural products export will show an empirical analysis based on the questionnaires of 100 staffs of agricultural trade companies.